Cyber criminals on trial - Smith, Russell G. (Cambridge University Press, 2004)
As computer-related crime becomes more important globally, both scholarly and journalistic accounts tend to focus on the ways in which the crime has been committed and how it could have been prevented. Very little has been written about what follows: the capture, possible extradition, prosecution, sentencing and incarceration of the cyber criminal. Originally published in 2004, this book provides an international study of the manner in which cyber criminals are dealt with by the judicial process. It is a sequel to the groundbreaking Electronic Theft: Unlawful Acquisition in Cyberspace by Grabosky, Smith and Dempsey (Cambridge University Press, 2001). Some of the most prominent cases from around the world are presented in an attempt to discern trends in the handling of cases, and common factors and problems that emerge during the processes of prosecution, trial and sentencing